Global city patterns in the wake of World Expos: A typology and framework for equitable urban development post mega-event. (August 2022) - Minner, Jennifer S.; Zhou, Grace Yixian; Toy, Brian
Abstract: International exhibitions, also known as world's fairs or international expos, are important examples of large-scale mega-events. Regulated and promoted by the Bureau of International Expositions, world and specialized expos are purported to aid in the achievement of urban development goals for host cities and nations. Scholars have focused analyses on the social and economic impacts of staging mega-events and in the immediate years after events. In this article, the authors consider the spatial and land use aspects of expo sites, developing a post-expo typology to aid in in-depth and comparative analysis of spatial patterns across sites and years after the mega-event. The authors then present a framework for equitable urban development, to consider the equity dimension of sustainability at former mega-event sites. The urban development typology is then considered with the equitable urban development framework, to propose interventions that are specific to particular expo types. The article links consideration of spatial land use patterns and expo legacies long after the first wave of urban development associated with staging an expo has passed. Highlights: World expo and specialized expo sites are understudied in mega-events literature. Expo sites should be studied in the long term and compared globally. Land use patterns at a large proportion of former expo sites were analyzed. A post-expo urban development typology was created to enable global comparisons. A framework for equitable urban development at expo sites is proposed.